GAMBARAN SUBJECTIVE WELL BEING PADA TENAGA KERJA GENERASI Y - Wicaksana, Seta A; Novasari, Estu Pratiwi; R, Nadhila Nunanisa; Asrunputri, Aisyah Pia (JURISMA : Jurnal Riset Bisnis & Manajemen, 2019)
Subjective well-being (SWB) is individual’s evaluation towards his life. SWB consists of three aspects: life satisfaction, positive affect and negative affect. A research conducted by Soto (2015) shows there is a reciprocal correlation between SWB and five personality dimensions (neuroticism, extraversion, openness, conscience and agreeableness). This research is consistent with a research by Diener that Subjective well-being is highly affected by personality (1999). A person with high SWB is high in extroversion, agreeableness, conscience and low in neuroticism. Objective of this research is to gain a picture of generation Y’s SWB through their personality assessment. This research involved 1107 participants, range from 18 – 37 years old. Personality is measured by NEO PI by Costa Mc Crae. The result shows generation Y is low in extraversion and openness; very low in agreeableness and conscience; and average in neuroticism. Based on the result we can conclude that generation Y’s SWB is tends to be low. Keyword: Subjective Well-being, personality, Costa-McCrae, Generation Y